Layanan Library and Knowledge Center (LKC) Bina Nusantara University di Era Pandemi Covid-19 - Syifa Naufal Qisty; Ninis Agustini Damayani; Elnovani Lusiana; Ilham Gemiharto; Ute Lies Siti Khadijah (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2021)
The covid-19 pandemic has succeeded in changing the order of life, one of which is in the field of libraries. This also changes the services carried out in the BINUS University library. The BINUS University Library has made several adjustments to some of its services. Services that are usually done in person and face-to-face are now done online. This online service is also an example of using computers as a medium for communication. This computer-mediated communication is reflected in several services and innovations carried out by the BINUS University library. This article aims to describe the services and innovations carried out by the BINUS University library. The method used is direct interview and literature study. The services provided by the BINUS University library are asynchronous, that is, they are carried out in a different time and space, and synchronous, that is, they are carried out in the same time and space. The results of the study show that several services and innovations have been carried out, such as reference clinics, cross-service services, document provision, and plagiarism checking, which are now also carried out online. Circulation services in the form of a book delivery system have also been improved during the pandemic. The BINUS University library has also made several innovations in its services in the pandemic era. These innovations include the payment of fines through Go-Pay and QRIS BCA, a virtual tour library service, and libtalks.